2013
DOI: 10.6018/analesps.29.1.124601
|View full text |Cite
|
Sign up to set email alerts
|

Autoeficacia en la prevención sexual del Sida: la influencia del género

Abstract: Resumen: La literatura científica apunta a que la escasa autoeficacia para el uso del preservativo explicaría muchas conductas de riesgo de transmisión del VIH en jóvenes. Se analiza la autoeficacia de los jóvenes en el uso del preservativo, la existencia de diferencias de género y la relación con variables relevantes en la prevención. Se aplicó la "Subescala de Autoeficacia en el Uso del Preservativo", incluida en el Cuestionario de Prevención del Sida (Ballester, Gil y Giménez, 2007), a 3540 universitarios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
18

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 16 publications
5
19
0
18
Order By: Relevance
“…People with high interpersonal skills, with tendency to think before acting, that consider potential consequences, are less likely to participate in risky sexual behaviors [63][64][65]. On the other hand, the importance of condom use self-efficacy has been demonstrated in many studies [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…People with high interpersonal skills, with tendency to think before acting, that consider potential consequences, are less likely to participate in risky sexual behaviors [63][64][65]. On the other hand, the importance of condom use self-efficacy has been demonstrated in many studies [27].…”
Section: Discussionmentioning
confidence: 99%
“…A person, whose cognitive self-evaluation or judgement of their capabilities is high, will tend to use a condom with greater confidence. Empirical evidence has demonstrated that people with high levels of condom use self-efficacy make successful decisions regarding sexual health, both ability to use condoms as ability to reject sexual risk behaviors [22,23,[26][27][28][29]67]. Self-efficacy is not a static characteristic, it can be altered by internal personal factors in the form of cognitive and affective events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A escolha pelo uso da camisinha está relacionada ao conhecimento inadequado, às práticas inseguras e atitudes que distorcem a realidade dos indivíduos analisados, gerando mudanças em seus planos de vida conjugais ou individuais. Um dos motivos que levam os casais a não usarem preservativos consiste no medo de que o parceiro pense que ele/ ela tem alguma doença sexualmente transmissível 16 .…”
Section: Tabela 2 -Teste Da Contribuição Das Variáveis Ao Modelounclassified
“…Así pues, no solamente hombres y mujeres divergen en las características que les exponen al riesgo de infección (Ballester et al, 2013;Lameiras et al, 2004;Navarro-Pertusa et al, 2003), sino también, en el cambio que muestran tras la participación en estrategias preventivas.…”
Section: Sexo Segurounclassified